Listening geographies: Landscape, affect and geotechnologies. (October 2017) - Gallagher, Michael; Kanngieser, Anja; Prior, Jonathan
This paper argues for expanded listening in geography. Expanded listening addresses how bodies of all kinds, human and more-than-human, respond to sound. We show how listening can contribute to research on a wide range of topics, beyond enquiry where sound itself is the primary substantive interest. This is demonstrated through close discussion of what an amplified sonic sensibility can bring to three areas of contemporary geographical interest: geographies of landscape, of affect, and of geotechnologies.